Measuring Brand Loyalty of Coffee Shop Visitors in Jakarta - Suhud, Usep; Puter, Cattleya Dewi; Wibowo, Setyo Ferry (ASEAN Marketing Journal, 2021)
This study is intended to investigate the impact of brand trust, brand affect, self-image congruity, and functional congruity toward brand loyalty of coffee shop visitors. Participants were approached conveniently in several modern coffee shops in August-September 2014 in southern Jakarta. In total, there are four hypotheses to be tested using 200 usable valid questionnaires. As a result, three hypotheses were accepted – the links between brand trust and brand loyalty, self-image congruity and functional congruity, and functional congruity and brand loyalty. This study suggests an alternative model in order to have all hypotheses significant and positive. Brand affect and self-image congruity should not be directly linked to brand loyalty concurrently. Coffee shop managements should consider brand trust and functional congruity as two important factors in maintaining brand loyalty.